Single Site Cannulation Veno-venous Extracorporeal Lung Support During Pulmonary Resection in Patients with Severely Compromised Pulmonary Function. Issue 3 (May 2015) - Redwan, Bassam; Semik, Michael; Dickgreber, Nicolas; Ziegeler, Stephan; Fischer, Stefan
<x xml:space="preserve">Abstract</x> The intraoperative application of extracorporeal lung support devices during thoracic surgical procedures represents a modern concept with promising results. So far, pumpless extracorporeal interventional lung assist and veno-venous or veno-arterial extracorporeal membrane oxygenation via dual cannulation were utilized for complete or partial lung support throughout the surgical procedure. We report the initial intraoperative application of low-flow singular double-lumen veno-venous-extracorporeal membrane oxygenation for extracorporeal lung support during lung resections in patients with severely impaired preoperative pulmonary function. In our hands, this novel concept contributed to the safe performance of complex surgery in pulmonary compromised patients avoiding the possible complications of other forms of extracorporeal support.